Selective Plant Extracts and their Combination as the Nutritional Therapeutic Remedies - G. Antoshechkin, Anatoly (Journal of Nutritional Therapeutics, 2016)
The article is a survey of some plant extracts that possess ability to restore metabolic disturbances evoked by chronic stress. Chronic stress triggers a number of common illnesses, including depression, chronic physical and mental fatigue, neuroses, cardiovascular diseases, ulceration of stomach and intestine, diabetes mellitus, obesity and alcohol abuse. One of the early consequences of chronic stress is the decrease of functional activity of immune system that reduces resistance against infections, allergies, asthma, autoimmune disorders, rheumatoid arthritis. The initial stages of chronic stress consequences are suppression of immune system, disturbances of hormonal balance, hydrocarbon, lipid, and energy metabolism. Applicability of the extracts from Leuzea carthamoides, Rhodiola rosea, Eleutherococcus senticosus, Schizandra chinensis and their combination “AdMax” to counteract the initial stages of chronic stress consequences is considered.